1975
DOI: 10.1079/bjn19750039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different feeds, including those containing soya-bean products, on the passage of digesta from the abomasum of the preruminant calf

Abstract: I. The effects of various factors on rates of flow and composition of digesta leaving the abomasum of preruminant calves were studied. The possible relation of some of these effects to the development of serum antibodies to certain dietary constituents has also been examined. Two situations were distinguished : (a) unsensitized responses, shown by calves receiving milk protein or soya-bean products for the first one or two occasions; (b) sensitized responses, shown by calves receiving certain soya-bean product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 34 publications
(7 reference statements)
4
42
0
Order By: Relevance
“…The secretory pattern after the ingestion of milk, as measured by the flow rate and the electrolyte concentrations, seems to indicate the presence in these animals of a continuous abomasal emptying and a consistently acid pH in the proximal duodenum. Experiments performed by Toullec et al (1971) and Smith and Sissons (1975) in calves, as well as those carried out by Hernandez-Clua et al (1988) in goat kids, evidence a continuous emptying of milk that lasts until the end of the 8 hours experimental period. Such emptying reaches maximum values during the first three postprandial hours.…”
Section: Discussionmentioning
confidence: 96%
“…The secretory pattern after the ingestion of milk, as measured by the flow rate and the electrolyte concentrations, seems to indicate the presence in these animals of a continuous abomasal emptying and a consistently acid pH in the proximal duodenum. Experiments performed by Toullec et al (1971) and Smith and Sissons (1975) in calves, as well as those carried out by Hernandez-Clua et al (1988) in goat kids, evidence a continuous emptying of milk that lasts until the end of the 8 hours experimental period. Such emptying reaches maximum values during the first three postprandial hours.…”
Section: Discussionmentioning
confidence: 96%
“…(1979) strggested that the reactions to soybean antigens in calves involved antigen-antibody reactions that activated complement, and the occurrence of such reactions on the intestinal mucosa adversely affected the integrity (Kilshaw and Slade 1980;Pedersen andSissons 1984: Silva et al 1986), and nutrienr absomtion abilitv (Sissons and Smith 1976; of the inrestine. Seegraber (Smith and Sissons 1975). In vitro studies have shown that antisenicitv can be reduced by either extruding or"fernrenting the meal with rumen fluid (Mir et al 1989).…”
mentioning
confidence: 99%
“…J. Anim. into the small intestine (Hill et al 1970 (Smith and Sissons 1975 .--{ \'u*-r:€tsXttbbs * R:: e 9q"1.1"? \ !q I !"?…”
mentioning
confidence: 99%